PENERAPAN TEHNIK INDIVIDUAL DALAM SUPERVISI AKADEMIK UNTUK MENINGKATKAN MUTU PEMBELAJARAN DI UPTD SMP NEGERI 12 KOTA KUPANG TAHUN PELAJARAN 2021/2022 - Elisabeth Lensi (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2022)
UPTD SMP Negeri 12 Kupang City shows the problem of the gap between expectations and the reality of administrative preparation and implementation of teacher learning in the classroom. The researcher formulates the school action research problem by asking: 1) how does the head of UPTD SMP Negeri 12 Kupang City act to improve teacher administration so that they are accustomed to collecting learning tools on time? 2) how do principals act to improve teacher teaching methods based on the preparation of qualified learning tools? The principal's action is to apply individual academic supervision techniques that are able to create an orderly culture of teacher administration in order to improve the quality of learning. This type of PTS is descriptive qualitative with a case study method variant. The PTS procedure begins with research planning, followed by implementation, observation and reflection on the learning data of the teachers of UPTD SMP Negeri 12 Kupang City. The findings of PTS are, first, teacher administration disorder. Second, the implementation of teacher learning is not in accordance with the preparation and planning. Third, it is necessary to increase the use of methods and the application of learning models in accordance with 21st century learning processes and models. From the results of the discussion of the findings, it can be concluded: first, the head of UPTD SMPN 12 Kupang City took steps to improve teacher administration to get used to collecting learning tools on time by: 1) holding a Workshop/In House Training every new academic year so that teachers prepare all learning tools ; 2) submit the deadline for the entry of learning devices before carrying out learning activities at the UPTD SMP Negeri 12 Kupang City; 3) In the future, giving rewards to fellow teachers who enter the learning tools on time according to the predetermined time limit. The second conclusion is that the principal acts to improve the way teachers teach based on the preparation of teaching and learning activities that meet the requirements according to quality learning by means of: (1) Encouraging teachers to apply quality learning techniques and creating a culture of administrative order to improve the quality of learning according to the demands of the times. Always updated in accordance with the development of 21st century learning demands; (2) Encouraging teachers to follow the learning systematics that have been prepared in the learning process: (3) Encouraging teachers to be creative and innovate in teaching and learning activities in the classroom. For example, using an IT-based and fun ICT learning model so that children feel happy in participating in the learning presented by the teacher (Student Wellbeing). So it is recommended (1) teachers have a high commitment to the implementation of duties and responsibilities in a professional manner (2) teachers must be able to distinguish between learning methods and learning media (3) Teachers prepare themselves as well as possible before learning activities in class (4) Principals carry out supervision every semester to remind learning activities and encourage teachers to move forward.